Roles and mechanisms of circular RNA in respiratory system cancers - Yang, Nan; Jiao, Mengwen; Zhang, Yuewen; Mo, Shaokang; Wang, Ling; Liang, Jianqing (Frontiers in Oncology, 2024)
Circular RNAs (circRNAs) constitute a class of endogenous non-coding RNAs (ncRNAs) that lack a 5'-ended cap and 3'-ended poly (A) tail and form a closed ring structure with covalent bonds. Due to its special structure, circRNA is resistant to Exonuclease R (RNaseR), making its distribution in the cytoplasm quite rich. Advanced high-throughput sequencing and bioinformatics methods have revealed that circRNA is highly conserved, stable, and disease-and tissue-specific. Furthermore, increasing research has confirmed that circRNA, as a driver or suppressor, regulates cancer onset and progression by modulating a series of pathophysiological mechanisms. As a result, circRNA has emerged as a clinical biomarker and therapeutic intervention target. This article reviews the biological functions and regulatory mechanisms of circRNA in the context of respiratory cancer onset and progression.